1975
DOI: 10.1097/00006842-197501000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Mechanisms for Cardiac Control by Nutritional Intake after Early Maternal Separation in the Young Rat

Abstract: Series of analytic experiments are presented that explore possible physiological mechanisms for the control of cardiac rate by nutritional intake in the pre-weanling rat. The essential properties of the nutrient and the first site of action were studied by using fluids of different pH, osmolality and chemical composition administered intravenously as well as intragastrically. Several probable effector pathways were explored: neuroendocrine (adrenal medullary and adrenocortical, thyroid), cholinergic and adrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…Other measures of sleep organization were not scored: the probabilities of transition from 1 particular state to another, measures of substates, the integration of the several physiological and behavioral components of the states, and the length of the average PS-PS cycle. In our previous study these measures were found not to be affected by separation from the mother (Hofer, 1975).…”
Section: Discussionmentioning
confidence: 71%
“…Other measures of sleep organization were not scored: the probabilities of transition from 1 particular state to another, measures of substates, the integration of the several physiological and behavioral components of the states, and the length of the average PS-PS cycle. In our previous study these measures were found not to be affected by separation from the mother (Hofer, 1975).…”
Section: Discussionmentioning
confidence: 71%
“…For example, neonatal sleep-wake cycles (Hofer, 1976;Hofer & Shair, 1982), ornithine decarboxylase levels (Butler, Suskind, & Schanberg, 1968;Evoniuk, Kuhn, & Schanberg, 1979;Kuhn, Butler, & Schanberg, 1978), normal adrenocortical activity (Smotherman, 1983;Stanton & Levine, 1984), heart rate (Hofer, 1971(Hofer, ,1973Hofer & Winer, 1975), and blood pressure (Shear, Brunelli, & Hofer, 1983) are all dependent upon maternal stimulation experienced by pups during normal contact with the dam. Also, Barnett and Walker (1974) have reported that stroking pups with a brush, a procedure used to mimic maternal stimulation, produces a decrease in pup surface body temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Sepa rated infant rats show a decrease in heart and respiratory rates (despite evidence of distress and increased motor activity) of 30% [50,51]. This decrease is due to a diminution of beta-adrenergic sympathetic tone.…”
Section: Early Social Experience Alters Behavior and Bodily Functionmentioning
confidence: 99%